Impact of the Holocene Transgression on the Atlantic Coastline of Nova Scotia - Shaw, John; Taylor, Robert; Forbes, Donald (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1993)
ABSTRACTAs analogs for impact of a future sea-level rise on the coast of Nova Scotia (eastern Canada), geological data and information on relative sea-level changes are examined at three different time scales. Relative sea level rose swiftly during the early Holocene, at a maximum rate of 11 m/ka at 7500 radiocarbon years BP. Freshwater, salt-marsh, and estuarine sediments that formed during this period have been located on the inner shelf. After 5000 BP the rate slackened to about 2 m/ka. Despite overall submergence and coastal retreat since that time, gravel barriers have persisted where large amounts of sediment have been added to the littoral system by erosion of glacial deposits. The barriers often display evidence of early progradational phases in the form of gravel beach ridges, partly or wholly submerged in lagoons behind contemporary storm beaches. Tide-gauge data from the past century show submergence rates averaging 3.5 mm/a, well in excess of the longterm trend. The response of the coastline to this rapid rise is complex. Unconsolidated cliffs (bluffs) retreat at up to 5 m/a during initial exposure to wave attack and during extreme storm events, but at lesser rates (<0.5 m/a) as protective beaches, lag shoals or boulder frames accumulate at the base of the cliffs. Beach retreat rates are sometimes very high (>8 m/a) in some locations, but low elsewhere, in some cases showing almost no movement over the past 10 years, and neighbouring beaches are sometimes observed to behave in completely different ways. Sediment released by coastal erosion finds its way into nearby estuaries, causing growth of flood-tidal deltas and marsh aggradation. If a global rise in sea level occurs, the processes of erosion and sedimentation operating along the coast of Nova Scotia during the Holocene are expected to continue in a similar fashion, but rates of change will increase at many locations.